THE EFFECTIVENESS OF ADDING SEAWEED TO FEED IN REDUCING FAT AND CHOLESTEROL LEVELS IN BROILER CHICKENS - Rosdiana Ngitung; Patma Elis (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
This study aims to determine the effectiveness of adding seaweed to feed in reducing fat and cholesterol levels in broiler chickens. This type of research is experimental. This research method used a completely randomized design (CRD) consisting of 4 treatments with three replications. The treatments given were Ration without the addition of seaweed (K), R1 (Ration with the addition of seaweed 7 %), R2 (Ration with the addition of 9% seaweed), and R3 (Ration with the addition of 11%). The parameters observed were a decrease in meat fat content, a decrease in cholesterol levels, and the live weight of broiler chickens. Fat content was measured using the Soxhlet method, and cholesterol levels were measured using the Esey Touch GCU. The data analysis technique used is the Analysis of Variance (ANOVA) at the confidence level = 0.05; if the ANOVA results show a significant difference, proceed with Duncan's further test. The results showed that adding seaweed to the feed reduced broiler chickens' fat and cholesterol levels. Treatment with the addition of 7% seaweed reduced the fat content of the meat and cholesterol levels in broiler chickens and did not reduce the live weight of broiler chickens. Meanwhile, the 9% and 11% treatments reduced meat fat content, cholesterol levels, and reduced live weight of broiler chickens. So it can be concluded that the addition of 7% seaweed proved effective in reducing broiler chickens' fat and cholesterol levels.